Pendidikan Lingkungan Hidup Melalui Gerakan Pembersihan Pantai di Pantai Payum Papua - Jua, Selestina Kostaria; Simangunsong, Ika Trisni; Maturbongs, Almendo Imanuel Cesar (Jurnal Budiman: Pembangunan dan Pengabdian Masyarakat Nusantara, 2023)
Developing countries such as Indonesia, have long struggled with environmental waste issues. Merauke also has trash problems, particularly in the Payum Beach area. Payum Beach has become a popular tourist destination, but unfortunately, the area is suffering from a lot of litter and pollution. This trash is feared to endanger the survival of Payum Beach’s biodiversity and ecosystem diversity. Concerns about the potential threat to public health from garbage have been raised. As a result, the community launched a beach cleanup movement to emphasize the significance of keeping Payum Beach clean. This service activity’s stages include situation analysis or survey, licensing process, service activity implementation, and activity evaluation. The cleanup effort at Payum Beach covered a distance of 700-800 meters from the starting point. During the cleanup activity, the volunteers collected nine pieces of plastic trash. I have corrected the grammar and punctuation errors. The trash was disposed of at the Merauke Waste Disposal Site (TPS). The final section is an evaluation, in which the service team returned to Payum Beach after one week of service implementation to assess the extent of the success of the beach cleanup movement.